Effects of lithium use on the white matter of patients with bipolar disorder - a systematic review - José Carlos Lobo Espanhol (2021)
Background: Several studies revealed changes in the microstructure of white matter in bipolar disorder patients. Lithium has been reported as having neuroprotective effects. However, its effect on white matter remains unclear. This systematic review aims to identify the existing clinical evidence of lithium's effect on the white matter from bipolar disorder patients. Methods: PRISMA guidelines were followed for a systematic literature review to assess the effect of lithium on the white matter of patients with bipolar disorder. From a total of 204 studies screened, 16 were included in the final systematic review. Quality assessment of the included records was assessed by the Newcastle-Ottawa scale. Results: Most studies included (13 out of 16) evaluated diffusion tensor imaging measures to assess white matter integrity. Of these, eleven reported a positive effect of lithium on the integrity of white matter of bipolar disorder patients. Two reported no effect. Two studies evaluated white matter volume. The first reported that lithium attenuates reduction of white matter volume over time, and the second reported significantly smaller white matter volume in non-lithium using patients. The last evaluated ventricular brain ratio and reported that patients treated with lithium did not have a significantly greater ventricular size than their normal control counterparts. Conclusions: Lithium appears to positively influence the evolution of the white matter abnormalities described in bipolar disorder patients. Should this information be confirmed in future research, and given its important mood stabilizer effect, it could further reinforce the use of lithium in the treatment of bipolar disorder.